1987
DOI: 10.1063/1.339140
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous vitrification in Cr-Ti bulk alloys

Abstract: We describe a new process that enables the formation of amorphous Cr40Ti60 cubelets with dimensions in the millimeter range by a sequence of standard metallurgical procedures. Vitrification occurs spontaneously during low-temperature furnace annealing. The resulting amorphous material contains small-grained crystalline inclusions. Mechanically, the process results in a marked increase of the microhardness and a decrease of the elastic modulus of the material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…7(b), 7(c) and 7(d)). The diffuse scattering observed in the present study is similar to those reported in the previously reports, 2,4,1922) and can be attributed to the mechanical instability and/or the ½ transition of the bcc phase. 4,20,26,27) The evolution of diffuse scattering during annealing indicates the decrease in the stability of the irradiated bcc solidsolution phase by annealing, however, the occurrence of SV cannot be seen.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…7(b), 7(c) and 7(d)). The diffuse scattering observed in the present study is similar to those reported in the previously reports, 2,4,1922) and can be attributed to the mechanical instability and/or the ½ transition of the bcc phase. 4,20,26,27) The evolution of diffuse scattering during annealing indicates the decrease in the stability of the irradiated bcc solidsolution phase by annealing, however, the occurrence of SV cannot be seen.…”
Section: Resultssupporting
confidence: 81%
“…The annealing temperature was fixed at 873 K on the basis of the results of the above thermal analysis and of previous reports. The formation of an amorphous phase through SV was previously reported for Ti 60 Cr 40 thin film annealed at 873 K, 1) for water-quenched Ti 60 Cr 40 alloy annealed at 873 K for 1.8 © 10 4 s, 2) for mechanically alloyed Ti 60 Cr 40 (obtained from an elemental powder blend of Ti 60 Cr 40 ) annealed at 823 K for 1.2 © 10 3 s, 17) and for mechanically alloyed Ti 50 Cr 50 annealed at 850 K for 1.8 © 10 3 s, 18) indicating that ex situ annealing at 873 K for a period on the order of 10 4 s was a suitable condition for the current experiment to determine whether SV actually occurs. The changes in the microstructure of the alloy were investigated using XRD and TEM, where the alloy was ex situ annealed at 873 K for various periods, and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this system, the high temperature bcc solid solution (fl-phase) is metastably frozen by temperature quenching. Only a moderate cooling rate is required, which allows the preparation of bulk fl-phase material [5]. A series of polymorphous transformations has been found to precede and accompany amorphization [6]: At a temperature TH between 370 and 450 ° C (depending on composition), alloys with 30M0 at.% Cr undergo an exothermic transition.…”
mentioning
confidence: 99%